A comparison of systemic inflammatory responses between immunocompetent and immunocompromised patients presenting with otorrhea due to chronic suppurative middle ear disease. (October 2015) - Sarmento, K.M.A.; Sampaio, A.L.L.; Nakanishi, M.; Gurgel, J.D.C.
<x xml:space="preserve">Abstract</x> Objectives To study the occurrence of fever and the behaviours of inflammatory blood markers (C‐reactive protein – CRP and procalcitonin – PCT) during episodes of otorrhea due to uncomplicated chronic otitis media in immunocompetent and immunocompromised patients. Design Prospective study of patients presenting with otorrhea over a 36‐month period. Setting All patients were treated at Bonsucesso General Hospital, a tertiary referral hospital in Rio de Janeiro, Brazil. Participants A total of 84 participants, of which 50 were immunocompetent and 34 were immunocompromised. Immunocompetent patients had a total of 106 episodes of otorrhea, and immunocompromised patients had 117 episodes of otorrhea. Main outcome measures Occurrence of fever (axillary temperature over 38°C) and elevation of C‐reactive protein and procalcitonin levels above the normal ranges. Results In the immunocompetent group, the levels of procalcitonin were elevated in five of 106 episodes of otorrhea. The C‐reactive protein levels were above the normal range in nine of 106 episodes, the same number of episodes in which fever was observed. In the immunocompromised group, procalcitonin was elevated in 38 of 117 episodes of otorrhea, C‐reactive protein levels were abnormal in 40 episodes, and fever was detected in 37 episodes. Cases of otorrhea with systemic inflammatory response were significantly more common in immunocompromised patients with associated rhinosinusitis. Conclusions Otorrhea due to uncomplicated chronic otitis media rarely causes a systemic inflammatory response in immunocompetent patients. Its occurrence in immunocompromised patients seems to be more related to concurrent rhinosinusitis than to the chronic middle ear inflammation itself.